2008
DOI: 10.1179/136485908x267867
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of loiasis in Ondo state, Nigeria, as evaluated by the rapid assessment procedure for loiasis (RAPLOA)

Abstract: The rapid assessment procedure for loiasis (RAPLOA) was used to assess the prevalences of loiasis among 4800 subjects in 60 villages in Ondo state, south-western Nigeria. Coverages for community-directed treatment with ivermectin (CDTI) were assessed in the same communities, which were located in the Owo, Akure North, Ifedore, Akure South, Ondo East and Ondo West local government areas (LGA). In addition, fingerprick blood samples were collected from 80 individuals in each of six villages (i.e. one village in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Female participants showed higher positive Loa microfilaria than males, which were not significantly different ( P >0.05) and could only suggest that females were more exposed to Chrysops vectors than males in the study area. On the contrary, earlier studies in Nigeria had reported that males were likely than females to present with Loa microfilaremia [11,26,27]. The mechanisms underlying the gender bias are still unknown; experimental infections in animal models have demonstrated gender differences in susceptibility to, or the development of, filarial infections [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female participants showed higher positive Loa microfilaria than males, which were not significantly different ( P >0.05) and could only suggest that females were more exposed to Chrysops vectors than males in the study area. On the contrary, earlier studies in Nigeria had reported that males were likely than females to present with Loa microfilaremia [11,26,27]. The mechanisms underlying the gender bias are still unknown; experimental infections in animal models have demonstrated gender differences in susceptibility to, or the development of, filarial infections [28].…”
Section: Discussionmentioning
confidence: 99%
“…Mectizan® has a major drawback, according to the Mectizan® Expert committee/The Mectizan® Donation Program and World Health Organization (WHO) [3,4], those suffering from onchocerciasis who simultaneously possess a high intensity of Loa loa infection could potentially suffer from severe adverse effects (SAEs), including neurological reactions, such as encephalopathy. Several studies reported distribution of L. loa and prevalences of human loiasis in the vegetational zones of Southwestern Nigeria [5-11]. Levels of adverse outcomes of treatment with ivermectin have been reported from areas of co-endemicity of onchocerciasis with loiasis or lymphatic filariasis [12-17].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the twelve communities selected from the three senatorial districts of the state for RAPLOA, 3(25%) communities, all located in Osun East Senatorial district had a prevalence of 40% and above (threshold value established by the RAPLOA development study). It is noteworthy that Osun/Ife East boarders Ondo State, Nigeria where high prevalence of Loa loa with intense biting of crysops in forest areas has been reported [ 20 ][ 21 ]. Also out of the twelve communities surveyed for L .…”
Section: Discussionmentioning
confidence: 99%
“…More so, accurate detection of the infection rates in vector populations is essential for assessing transmission, deciding when drug treatments may be stopped, and monitoring recrudescence [12]. Several studies have documented reduction of the prevalence and intensity of loiasis in the human population after treatment with Ivermectin [13][14][15][16]; however, there is little information about the infection rate of the vectors after chemotherapy. In a well organised control program where Ivermectin would deplete micro lariae in the host, Chrysops ies would tend to take up lower numbers of mf in their blood meals.…”
Section: Introductionmentioning
confidence: 99%